Analisis Nilai Tambah Agribisnis Kopi Arabika di Kecamatan Doloksanggul, Kabupaten Humbang Hasundutan, Sumatera Utara (Studi Kasus: Pedagang Besar Si Talbak Coffee) - Widiawati, Dewi; Renaldi, Eddy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Indonesia is the fourth-largest coffee producer in the world, with a production of 774,689 tons in 2021, with the Doloksanggul District being one of the centers of Arabica coffee production located in Humbang Hasundutan Regency, North Sumatra. The Arabica coffee agribusiness in Doloksanggul District involves many actors who add value to the product through various processing methods, impacting the economic value of the product and the rewards for labor and business owners. This study analyzes the added value generated by Si Talbak Coffee, a major trader in Doloksanggul, from processing coffee cherries into green beans, roasted beans, and ground coffee. The research method used is descriptive analysis and added value analysis using the Hayami method. The calculation of added value using the Hayami method shows that the total added value obtained by the major trader from various processed products is Rp. 69,011 per kilogram, with the highest added value obtained from ground coffee production at Rp. 44,470 per kilogram, followed by green bean production at Rp. 12,871 per kilogram and roasted bean production at Rp. 11,670 per kilogram.